A study of the adjustment of relocated families in Palaca relocation site, Miag-ao, Iloilo. - Horlador, Candelaria (1983.)
In spite of the medical advances and the intensive health programmes, Philippines continues to have high infant mortality rate. The study was conducted with the following objectives: to know the socio-demographic profile of families with infants who died of preventable and communicable diseases between 1990-1995; To know the copules' family planning practices; and to describe the health care practices of the mothers. Mothers of the deceased infants serve as the respondents. The data were collected on an interview schedule and anlyzed using simple frequency counts and percentages., Major findings of the study showed that a great number of the couples have finished first year high school at most, got married at an early age, and have at least 6 children, including those who died . The spouses' employment opportunities were limited mostly to being a farmer's laborer while most respondents were housewives who did not engage in any income earning activity. As a result of this, majority of the families were below the monthly poverty threshold level. The study also showed that majority of the respondents did not use any birth control, had no intention of spacing their pregnancies, and got pregnant with the deceased infants in less than 2 years. The data showed that most respondents gave birth at home and had incomplete immunization and their primary cause of death was diarrhea followed by brochopneumonia. Based on the results, it was recommended that health officials should maintain and intensify their health programs. For further studies, the study be made into a correlational one and include other variables
Research Paper (Undergraduate, Bachelor of Arts in Social Science) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo
Keywords: Palaca Relocation Sites; Families, Relocated